Population dynamics of fruit flies (Diptera: Tephritidae) in a semirural area under subtropical monsoon climate of Bangladesh - Mahfuza Momen; Md. Aftab Hossain; Kajla Seheli; Md. Forhad Hossain; Md. Abdul Bari (Scientific Reports)
Abstract Fruit flies belonging to Tephritidae family are highly destructive agricultural pests, posing a significant threat to various fruits and vegetables grown in Bangladesh. A comprehensive year-round survey was conducted at Atomic Energy Research Establishment (AERE) campus located in the central region of Bangladesh. Three types of male lures (methyl eugenol, cue-lure and zingerone) were used to detect and assess the diversity of pest fruit fly species. A total of seventeen species of Tephritidae fruit flies were detected in this survey. The Bactrocera carambolae fruit fly has been discovered for the first time in our survey area, indicating spread of its range towards the north-west region from its previous detection sites (Chattogram and Sylhet Divisions) in Bangladesh. Among the detected pest species, we identified six abundant species: Bactrocera dorsalis, Zeugodacus cucurbitae, Zeugodacus tau, Bactrocera rubigina, Bactrocera zonata, and Dacus longicornis. The most abundant species was the polyphagous fruit pest B. dorsalis, comprising 76.83% of the total captured flies. The species Z. cucurbitae was the second most abundant, representing 13.82% of the total trapped flies. The fitted curve to survey data using Gaussian mixture model revealed the existence of overlapped subgroups in the temporal population distribution of B. dorsalis and Z. cucurbitae. In addition, our statistical analysis of the six abundant Tephritidae fruit fly species revealed correlation of population dynamics with several factors including temperature, rainfall, humidity, photoperiod, and fruiting time of host plant species in the selected area.